PENERAPAN METODE DISCOVERY LEARNING TERHADAP KEMAMPUAN SOSIAL EMOSIONAL MINAT BELAJAR PADA PEMBELAJARAN IPA DI KELAS V - Dwi Dini; A.Heriyanto; Sunedi (STKIP Subang, 2023)
The purpose of this study was to determine the application of the discovery learning method to the social emotional abilities of students’ learning interests at SD Negeri 08 Gelumbang. The subjects in this study were students of SD Negeri 08 Gelumbang, totaling 31 students. The method used is descriptive qualitative which, annalyzes data using observation, questionnaires and documentation. Based on the results of the study that a student’s social emotional abilities are good so they have an interest in learning, where from the distribution of the questionnaire students get good student responses with the final result of an average questionnaire score of 80, with good criteria. From the results of the questionnaire distribution, the percentage of students was obtained, where 2 students had fairly good criteria with a percentage of 60%, and 6 students had very good criteria with a percentage of 30%.